2010
DOI: 10.1111/j.1365-3040.2010.02234.x
|View full text |Cite
|
Sign up to set email alerts
|

A new, vapour‐phase mechanism for stomatal responses to humidity and temperature

Abstract: A new mechanism for stomatal responses to humidity and temperature is proposed. Unlike previously-proposed mechanisms, which rely on liquid water transport to create water potential gradients within the leaf, the new mechanism assumes that water transport to the guard cells is primarily through the vapour phase. Under steady-state conditions, guard cells are assumed to be in near-equilibrium with the water vapour in the air near the bottom of the stomatal pore. As the water potential of this air varies with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 33 publications
5
123
0
Order By: Relevance
“…Very little is known about the direct effect of temperature on stomatal conductance (g s ) 6 which may exist independently from indirect mechanisms. 7,8 Results of experiments that examined the direct dependence of stomatal conductance on temperature have not been consistent. Previous studies have reported a complete range of responses to increased temperature, including stomatal opening, [9][10][11][12] no significant response, [13][14][15][16] stomatal closure, [17][18][19] peaked response with maximum g s at temperatures optimal for photosynthesis 20 or more complex responses.…”
Section: Textmentioning
confidence: 99%
“…Very little is known about the direct effect of temperature on stomatal conductance (g s ) 6 which may exist independently from indirect mechanisms. 7,8 Results of experiments that examined the direct dependence of stomatal conductance on temperature have not been consistent. Previous studies have reported a complete range of responses to increased temperature, including stomatal opening, [9][10][11][12] no significant response, [13][14][15][16] stomatal closure, [17][18][19] peaked response with maximum g s at temperatures optimal for photosynthesis 20 or more complex responses.…”
Section: Textmentioning
confidence: 99%
“…The conclusions of syntheses of eddy covariance measures of the seasonality of E in the Amazon have largely emphasized the secondary role of vegetation demand across a range of forest types (Costa et al, 2004;Juarez et al, 2007;da Rocha et al, 2002da Rocha et al, , 2009Fisher et al, 2009), but recent work suggests that forests indeed exhibit varying degrees of control on the seasonal exchange of water in their canopies (Costa et al, 2010). Much of what is known about the functioning of stomata remains phenomenological; at the leaf-level, attempts at forming a solid mechanistic basis of stomatal function have proven to be a challenge (Buckley, 2005;Peak and Mott, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Wang et al (2017) take this approach and, in the process, unify the macroscopic water relations and evapotranspiration of the whole plant with the microscopic events of subcellular transport in the guard cells. They extend the quantitative OnGuard systems platform by incorporating the concept of a VPD gradient that extends through the stomatal pore and into the substomatal cavity adjacent to the guard cells (Peak and Mott, 2011). OnGuard is a proven computational platform for modeling stomatal physiology that encompasses guard cell transport, signaling, and homeostasis, and has predicted stomatal behavior across species (Chen et al, 2012;Wang et al, 2012).…”
mentioning
confidence: 99%